2016
DOI: 10.1371/journal.pntd.0004704
|View full text |Cite
|
Sign up to set email alerts
|

Using Rapid Diagnostic Tests as a Source of Viral RNA for Dengue Serotyping by RT-PCR - A Novel Epidemiological Tool

Abstract: BackgroundDengue virus infection causes major public health problems in tropical and subtropical areas. In many endemic areas, including the Lao PDR, inadequate access to laboratory facilities is a major obstacle to surveillance and study of dengue epidemiology. Filter paper is widely used for blood collection for subsequent laboratory testing for antibody and nucleic acid detection. For the first time, we demonstrate that dengue viral RNA can be extracted from dengue rapid diagnostic tests (RDT) and then subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Our report confirms previous observations where viral detection was reported to be more efficient with whole blood as compared to plasma (Klungthong et al, 2007). Dengue serotyping using rapid diagnostic tests have also demonstrated the convenience and utility of using whole blood for isolation of viral RNA (Vongsouvath et al, 2016). Another study which used cellular components of whole blood, serum, clot specimens and plasma from blood bank donors who were DENV RNA positive also demonstrated that the detection of viral RNA by RT-PCR was more consistent with cellular components of blood (Añez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our report confirms previous observations where viral detection was reported to be more efficient with whole blood as compared to plasma (Klungthong et al, 2007). Dengue serotyping using rapid diagnostic tests have also demonstrated the convenience and utility of using whole blood for isolation of viral RNA (Vongsouvath et al, 2016). Another study which used cellular components of whole blood, serum, clot specimens and plasma from blood bank donors who were DENV RNA positive also demonstrated that the detection of viral RNA by RT-PCR was more consistent with cellular components of blood (Añez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these specialized laboratories are all located in the capital, Vientiane, and there are limited cold chain facilities to transport samples from rural areas. 15 In those areas, the use of immunochromatographic rapid diagnostic tests (RDTs) for dengue diagnosis has recently expanded. Therefore, as a potential solution, Vongsouvath and others showed that RDTs, which are transportable at room temperature, can be used as a source for DENV RNA for small-fragment amplification using real-time reverse transcription polymerase chain reaction (RT-qPCR).…”
mentioning
confidence: 99%
“…Therefore, as a potential solution, Vongsouvath and others showed that RDTs, which are transportable at room temperature, can be used as a source for DENV RNA for small-fragment amplification using real-time reverse transcription polymerase chain reaction (RT-qPCR). 1517…”
mentioning
confidence: 99%
See 2 more Smart Citations